PENGARUH DISKON DAN PENGALAMAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION SHOPEE DI KECAMATAN CISAAT - MULFI SANDI (JSE: Jurnal Sharia Economica, 2026)
The development of e-commerce in Indonesia shows rapid growth, especially in the fashion product category, which is one of the sectors with the highest transaction rates on digital platforms. This condition encourages consumers to be more selective in making purchasing decisions by considering various factors that influence consumption behavior. Discounts are one of the effective marketing strategies in attracting consumer interest, while customer experience plays an important role in building satisfaction, comfort, and trust in online shopping platforms. This phenomenon is also seen among Shopee platform users in Cisaat District, who are increasingly active in purchasing fashion products online. This study aims to analyze the influence of discounts and customer experience on fashion product purchasing decisions on the Shopee platform in Cisaat District. The research method used is a quantitative approach with a survey method through the distribution of questionnaires to 100 respondents selected using purposive sampling techniques. Data analysis was performed using multiple linear regression with hypothesis testing through t-tests, F-tests, and determination coefficients. The results of the study indicate that discounts and customer experience, both partially and simultaneously, have a positive and significant effect on purchasing decisions. These findings confirm that the right discount strategy and improving the quality of customer experience can be important factors in driving consumer purchasing decisions on e-commerce platforms.